Taiwan: from Self-Determination to Negotiating Identities? - Sondaitė-Van Soest, Rima (Acta Orientalia Vilnensia, 2001)
This paper sets out to explore how the alternative conceptualizations of national identity influence the interpretation of the national self-determination principle in Taiwan. It will be argued that major disagreements about the application of the self-determination principle to Taiwan reflect the political priorities of different ethnic groups. An analysis of the political importance of historical imaginations is performed to demonstrate the ways the visions of the nation are endorsed and contested. It is concluded that the overlapping nationalities (Chinese and Taiwanese) and the lack of consensus in Taiwan inhibit the principle of the self-determination being put into political practice.